Edukasi dan Promosi Kesehatan Autis di Panti Asuhan SLB-C St.Lucia Lau Dendang Kabupaten Deliserdang - Noradina Noradina; Meriani Herlina; Rostinah Manurung; Mira Indrayani; Aureliya Hutagaol; Bernita Silalahi; Arta Marisi Dame; Paskah Rina Situmorang; Dea Lisa Sriananda Ritonga; Elena Laure Hasibuan; Yoga Saputra Gea; Putri Mulia Nanda; Muliyadi Banjar Nahor; Permanda Maulana (PPNI UNIMMAN, 2024)
Autism Education and Health Promotion at the St. SLB-C Orphanage. Lucia Lau Dendang, Deliserdang Regency” focuses on delivering autism education and health promotion aimed at improving educational and health outcomes for orphaned children with Autism Spectrum Disorder. Aim: this implementation is to improve knowledge and management of autism among staff and residents of residential care, to advance the development of individual skills in children with ASD, and to improve their physical, mental and emotional well-being. Methods: A multidisciplinary approach was adopted, featuring individualized education plans, specific teaching methods, health promotion activities such as regular physical exercise, nutritional education, and hygiene practices, alongside targeted mental health support. Expected Results: Benefits include increased autism awareness, improved communication and social interaction skills for children, better physical health through structured exercise and diet, and increased emotional stability from various coping strategies. In addition, this initiative aims to foster a safe and supportive environment that meets the sensory and safety needs of children with Autism. The implementation of this activity shows how important adaptive and holistic parenting models are in special needs orphanages and suggests that with training and resources appropriately, significant improvements in the quality of life of orphaned children with Autism can be achieved.